Pemanfaatan Teknologi Informasi dan Edukasi Gizi Menggunakan Aplikasi Gizi Anakku untuk Pencegahan Stunting di Desa Makmur - Sherllia Sofyana; Gabriella Sakulat; Matius Paundanan (ABDI WIDYA NUSANTARA: Jurnal Pengabdian Kepada Masyarakat, 2025)
Stunting is a chronic nutritional problem that affects children's growth and cognitive development. This community service activity aimed to improve nutritional literacy and the use of the "Gizi Anakku" application in Desa Makmur, Palolo District. The implementation methods included counseling, application training, and evaluation. The results showed an increase in mothers' understanding of balanced nutrition and their ability to use the application effectively. The use of technology proved to be effective in reaching rural communities. This application can serve as an educational strategy for stunting prevention